Soft Power: Definitions and Applications in the Context of Thailand - Polanan, Mallika (Executive Journal, 2025)
Presently, the concept of soft power is being used as a significant tool to drive Thailand’s economy. This has led to a wide debate that focuses only on what can be promoted as soft power, without a detailed study and a lack of profound understanding of the meaning of soft power. Soft power is defined as the occurrence of behavior that uses something because it is consistent with one’s needs and is seen as useful, through the process of persuasion, attraction, and popularity, leading to voluntary use without the use of force. In Thailand, culture is often defined as a resource that can be transformed into soft power, such as Thai food, Thai boxing, Thai clothing, and festivals related to local traditions and culture. However, there are also resources in other dimensions that can be developed into soft power, such as gender equality, environmental sustainability, democracy, and scholarships for international students. If the development of the resources mentioned above is coupled with the development of cultural resources, Thailand will have a diversity of soft power resources that can become a national brand, create recognition, build reputation, and create international acceptance until other countries use it or follow suit. These things can create a competitive advantage in the global market. The development of soft power resources requires strategic planning, with clear goals and the creation of mechanisms that support the improvement of soft power by focusing on SMEs. Mechanisms that enable the development of soft power include promoting future-needed skills, appropriate budget allocation, providing easily accessible sources of finance, and changing some regulations that do not promote the development of soft power.